Diversity and Multiple Infections of Bartonella in Red Deer and Deer Keds - Hammerbauerová, Iva; Richtrová, Eva; Kybicová, Kateřina; Pajer, Petr; Votýpka, Jan (Pathogens (Basel, Switzerland), 2024)
Bartonellae are zoonotic pathogens with a broad range of reservoir hosts and vectors. To examine sylvatic Bartonella reservoirs, tissue samples of red deer (Cervus elaphus, n = 114) and their associated deer keds (Lipoptena cervi, n = 50; L. fortisetosa, n = 272) collected in the Czech Republic were tested for the presence of Bartonella using PCR at four loci (gltA, rpoB, nuoG, ITS); PCR sensitivity was increased significantly by using primers modified for the detection of wildlife-associated bartonellae. One-third of the deer and 70% of the deer keds were Bartonella positive; within the tested animal tissues, usually the spleen was positive. The most prevalent Bartonella represents an undescribed species related to isolates from Japanese sika deer and L. fortisetosa. Additionally, B. schoenbuchensis sensu lato and B. bovis were found, together making up 17 genotypes characterized by multi-locus sequence typing, all unique compared to previously published sequences. Nanopore sequencing of selected samples revealed an additional 14 unique Bartonella genotypes, with up to six genotypes co-infecting one deer, highlighting the diversity of ruminant Bartonella. The high COI variety of examined L. cervi and L. fortisetosa suggests L. fortisetosa in central Europe is not a homogenous invasive population.
Keywords: zdroje nemoci; deer; genotyp; DNA, Bacterial; Bartonella; Genotype; Česká republika; polymerázová řetězová reakce; Polymerase Chain Reaction; genetická variace; vysoká zvěř; Czech Republic; Bartonella Infections; DNA bakterií; Genetic Variation; Multilocus Sequence Typing; zvířata; Lipoptena; zoonosis; fylogeneze; infekce bakteriemi rodu Bartonella; Deer; Disease Reservoirs; multilokusová sekvenční typizace; Phylogeny; Animals